2016
DOI: 10.14336/ad.2016.0309
|View full text |Cite
|
Sign up to set email alerts
|

Bulbocavernosus Reflex Test for Diagnosis of Pudendal Nerve Injury in Female Patients with Diabetic Neurogenic Bladder

Abstract: The study was designed to investigate the clinical application and significance of the bulbocavernosus reflex (BCR) test for diagnosing diabetic neurogenic bladder (DNB) in female subjects. In this study, 68 female patients with DNB and 40 female normal controls were subjected to a nerve conduction study (NCS) of all four limbs and the BCR test. The data were analyzed and compared, and the corresponding diagnostic sensitivities were discussed. Mean BCR latency for female DNB patients was significantly prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…The BCR follows the sacral reflex arc, and its latency reflects the integrity of pudendal sensory afferent nerve, sacral S2-4, and efferent motor fibers [ 10 ]. Over the past 20 years, BCR has been used for the diagnosis of various neurogenic disorders, including neurogenic impotence, diabetic neurogenic bladder, spinal shock, and cauda equina syndrome [ 15 , 16 ]. Cai et al [ 17 ] used BCR for the differential diagnosis of PD and MSA for the first time, and found that BCR latency could be used as an electrophysiological index to differentiate MSA from PD.…”
Section: Discussionmentioning
confidence: 99%
“…The BCR follows the sacral reflex arc, and its latency reflects the integrity of pudendal sensory afferent nerve, sacral S2-4, and efferent motor fibers [ 10 ]. Over the past 20 years, BCR has been used for the diagnosis of various neurogenic disorders, including neurogenic impotence, diabetic neurogenic bladder, spinal shock, and cauda equina syndrome [ 15 , 16 ]. Cai et al [ 17 ] used BCR for the differential diagnosis of PD and MSA for the first time, and found that BCR latency could be used as an electrophysiological index to differentiate MSA from PD.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, observamos que la diabetes mellitus tipo 2 podría estar relacionada con la ausencia del RBCV, pudiéndose asociar a lesión del nervio pudendo, como lo describieron Niu et al 11 al encontrar una prolongación en la latencia del RBCV en pacientes con diabetes.…”
Section: Discussionunclassified
“…La vejiga neuropática secundaria a diabetes está asociada con neuropatía periférica en 75% a 100% de los casos. 11 Las diferencias encontradas en nuestra población muestran la utilidad de una prueba accesible para determinar, de forma indirecta, si existe afección neuropática de la vejiga en pacientes con diagnóstico de diabetes, evaluando así la integridad del nervio pudendo. 11 Las perspectivas futuras están orientadas a validar la evaluación clínica del RBCV y su comparación con la estimulación eléctrica y la medición de su período de latencia, además de su estudio en la diversa gama de afecciones del piso pélvico en mujeres y hombres.…”
Section: Discussionunclassified
“…Prolonged BCR latency is associated with a pudendal nerve injury in females, and a longer clinical course of nerve injury may extend this latency. [ 12 ] The BCR latency in this patient (50 ms) was longer than the normative value, suggesting pudendal nerve injury[ 4 ] and potentially reflecting the interval from onset to treatment. It is reported that myelopathy could damage spinal motor neurons with faster conduction velocity and affect the synapses between the corticospinal tract and spinal motor neurons.…”
Section: Discussionmentioning
confidence: 99%